Fibroblast-Like Synoviocytes Glucose Metabolism as a Therapeutic Target in Rheumatoid Arthritis - de Oliveira, Patricia Gnieslaw; Farinon, Mirian; Sanchez-Lopez, Elsa; Miyamoto, Shigeki; Guma, Monica (Frontiers in Immunology, 2019)
Metabolomic studies show that rheumatoid arthritis (RA) is associated with metabolic disruption that may be therapeutically targetable. Among them, glucose metabolism and glycolytic intermediaries seem to have an important role in fibroblast-like synoviocytes (FLS) phenotype and might contribute to early stage disease pathogenesis. RA FLS are transformed toward overexpression of enzymes which degrade cartilage and bone, and cytokines which promote immune cell infiltration. Several glycolytic inhibitors have been shown to reduce not only FLS aggressive phenotype in vitro but also decrease bone and cartilage damage in several murine models of arthritis. Essential glycolytic enzymes, including hexokinase 2 (HK2) and 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFKFB) enzymes, have important roles in FLS behavior. Of interest, HK2 is an inducible enzyme present only in the inflamed rheumatic tissues compared to osteoarthritis synovium. It is a contributor to glucose metabolism that could be selectively targeted without compromising systemic homeostasis as a novel approach for combination therapy independent of systemic immunosuppression. More information about metabolic targets that do not compromise systemic homeostasis or corresponding metabolic functions in normal cells is needed.